2018
DOI: 10.1016/j.polymer.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced physical aging rates of polylactide in polystyrene/polylactide multilayer films from fast scanning calorimetry

Abstract: The physical aging behavior of amorphous polylactide constrained against polystyrene in layers of 300 nm, thanks to the layeremultiplying coeextrusion process, was investigated by fastescanning calorimetry (FSC). By cooling down the sample from the liquid state to the glassy one at very fast scanning rates, it was possible to investigate the structural relaxation of the polymer glass at high temperatures for which the time needed to reach the equilibrium was shortened. Therefore it was possible to perform the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…The quantity of recovered enthalpy at the longest aging times was near to the estimated total enthalpy loss, which showed that the theoretical thermodynamic equilibrium (within the measurement uncertainty) was reached within the experimental time. The H Δ values of PLA reached after 1000 min aging are comparable to already published data [31][32][33]. The curves in Fig.…”
Section: Glass Transition and Physical Aging Of Pla Pla/zno_r And Plsupporting
confidence: 89%
“…The quantity of recovered enthalpy at the longest aging times was near to the estimated total enthalpy loss, which showed that the theoretical thermodynamic equilibrium (within the measurement uncertainty) was reached within the experimental time. The H Δ values of PLA reached after 1000 min aging are comparable to already published data [31][32][33]. The curves in Fig.…”
Section: Glass Transition and Physical Aging Of Pla Pla/zno_r And Plsupporting
confidence: 89%
“…Sample mass was determined by doing the comparison between the heat capacity step ΔCp obtained from the glass transition in MT-DSC and FSC on a sample at the amorphous state. More details regarding the recommended protocol for FSC analysis of multilayer samples were given in the work of Monnier et al [35].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…It is also well suited for studying structural recovery , and early stages of polymer degradation . It offers the possibility to magnify changes in recovery kinetics due to structural constraints, which could become a criteria for investigation of macromolecular alignment. In addition, this technique has shown great potential for investigating thermal events in material for which degradation under standard DSC conditions can occur.…”
Section: Emerging Techniques For Evaluation Of Orientationmentioning
confidence: 99%